The Relationship Between Age, Height, and Knowledge Level Of Mothers With The Incidence Of Stunting In Toddlers - Yundelfa, Mandria; Rita, Nova; Nurhaida; Refialdinata, Jeki; Aldian Syaputra, Yoga (Rajaki of Tulip Medika Publisher, 2024)
Stunting is a condition where a child’s height is shorter than other children of the same age due to chronic malnutrition. Stunting is caused by age, height, mother’s education level, mother’s knowledge about nutrition, mother’s work, family income, parenting patterns and so on. The purpose of this study was to determine the relationship between age, height, and level of maternal knowledge with the incidence of stunting in toddlers. This type of research is a descriptive method with a cross-sectional approach. This research was conducted on June 27 to July 4, 2023. Which was conducted at the Ikur Koto Health Center, Padang City. The population in this study were all mothers who had toddlers in the Ikur Koto Health Center Working Area as many as 849 people. Sampling using Multistage Random Sampling technique with slovin formula which amounted to 89 respondents. Data analysis used is univariate and bivariate analysis.The results showed that most respondents (64%) were at risk. Most respondents (94.4%) have a non-short body. Most of the respondents’ knowledge level (44.9%) is not good. And most toddlers (94.4%) are not stunted. Statistical tests concluded that there was a relationship between age, height and level of maternal knowledge with the incidence of stunting in toddlers. It is hoped that health centers and other health facilities can pay attention and further optimize the provision of education and counseling about stunting, especially to further explain the prevention that can minimize the incidence of stunting with direct counseling at home.